2012
DOI: 10.1016/j.neuroscience.2012.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery of antioxidant enzymes inhibits human immunodeficiency virus type 1 gp120-induced expression of caspases

Abstract: Caspases are implicated in neuronal death in neurodegenerative and other Central Nervous System (CNS) diseases. In a rat model of HIV-1 associated neurocognitive disorders (HAND), we previously characterized HIV-1 envelope gp120-induced neuronal apoptosis by TUNEL assay. In this model, neuronal apoptosis occurred probably via gp120-induced reactive oxygen species (ROS). Antioxidant gene delivery blunted gp120-related apoptosis. Here, we studied the effect of gp120 on different caspases (3, 6, 8, 9) expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…This formation activates caspase-9-mediated apoptotic signaling cascades during neurodegeneration (Fratiglioni and Wang, 2000). HIV-1 proteins trigger the apoptotic signaling cascades by decreasing the levels of antioxidant enzymes with uncompensated ROS production (Louboutin et al , 2012). Our results partially confirm the aforementioned findings and show that HIV-1 proteins decreased the expression of antioxidant enzymes in the NAc (Gstm5) and up-regulated the Gsta6 in the VTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This formation activates caspase-9-mediated apoptotic signaling cascades during neurodegeneration (Fratiglioni and Wang, 2000). HIV-1 proteins trigger the apoptotic signaling cascades by decreasing the levels of antioxidant enzymes with uncompensated ROS production (Louboutin et al , 2012). Our results partially confirm the aforementioned findings and show that HIV-1 proteins decreased the expression of antioxidant enzymes in the NAc (Gstm5) and up-regulated the Gsta6 in the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between oxidant species and removal of oxidants by the antioxidant enzymes determines the ROS-mediated apoptosis signaling in neurons. Multiple in vitro and in vivo studies have demonstrated the neuroprotective effect of Sod1 overexpression in neurodegeneration including HAND (Boven et al , 1999; Louboutin et al , 2012). Results demonstrated that increased levels of Sod1 induced a decrease in ROS levels that lead to an enhanced resistance to caspase-mediated apoptosis in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is pGSN blocks the interaction between gp120 and Kv2.1 channel as viral proteins were found to interact with ion channels (Qiao and McMillan, 2007). In addition, pGSN may protect neurons through inhibition of gp120-mediated activation of caspases since gp120 has been shown to induce neuronal injury via activation of caspases (Louboutin et al, 2012; Tun et al, 2007) and GSN has been reported to, in complex with phosphatidylinositol 4, 5-biphosphate, inhibit caspase activity and retard apoptotic progression (Azuma et al, 2000). As to the site of pGSN action, it appears that pGSN acts extracellularly since pGSN inhibited gp120-induced shift of outward K + current inactivation curve shortly after brief bath perfusion of pGSN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of these two types of drugs is closely connected. Researchers are studying the interactions of different neurotransmitters [103], neurohormones [104], neuromodulators [105], enzymes [106], second messengers [107], co-transporters [108,109], ion channels [110], and receptor proteins [111] in the central and peripheral nervous systems to develop drugs to treat many different neurological disorders, including pain [112], neurodegenerative diseases such as Parkinson's disease [113] and Alzheimer's disease [114], psychological disorders [115], addiction [116], and many others.…”
Section: Nervous System Nanodrugsmentioning
confidence: 99%